"Like walking barefoot on the gravel road" : the experience of caring for a child with physical disabilities - Ndlovu, Nokanyo (Rhodes University, Faculty of Humanities, Department of Psychology, 2019)
The aim of this study was to develop an understanding of the experiences of caregivers of children with physical disabilities and to explore ways of improving this experience. Although there is a considerable amount of international research on the experiences of caring for children with disabilities, the focus of the methods of enquiry has mainly been on knowledge production and there is limited research conducted using an approach like participatory action research. Secondly, in South Africa, there is still inadequate information regarding the experiences of caregivers who are from low socio-economic backgrounds. It is for these reasons that the current study, which employed PhotoVoice, a participatory research data collection tool, to explore the lived experiences of caregivers of children with physical disabilities from low socio-economic backgrounds was embarked upon. The research methodology comprised two main parts: firstly, a study of relevant literature on the subject matter, in order to gain in-depth understanding of the field; and secondly, qualitative data collection, using PhotoVoice. A sample of six participants between the ages of 22-57 years was selected through purposive and convenience sampling. Cameras were distributed to participants and after processing of images narratives were shared around selected photographs and this was later followed by focused group discussions. This analysis process provided two master themes, which are supported by subordinate themes. The master themes are: 1) The challenges associated with the caregiving experience, 2) The positive side of the caregiving experience. Participants experienced a lack of resources, challenges of mobility, the hopelessness of the situation, loneliness of the experience and the financial burden of caring for a child with physical disabilities as challenges associated with the caregiving role. Whereas the joy brought about by support from family, the health service providers and the Association for People with Physical Disabilities personnel; precious moments shared with the child; and personal growth were associated with the positive side of the caregiving experience. These findings support and expand on the growing knowledge of caring for children with physical disabilities. This research culminated in a sharing of the narratives with stakeholders by caregivers themselves as a way of seeking to influence policy, enhance their well-being and engage in a discussion of exploring ways of improving their experience.
Keywords: PhotoVoice; Photography in the social sciences; Action research; Children with disabilites -- Care -- South Africa; Children with disabilites -- Care -- South Africa -- Case studies; Caregivers -- South Africa -- Case studies; Caregivers -- South Africa